Pengaruh Fitur Live Shopping, Interaktivitas Host Terhadap Minat Beli (Studi Kasus pada ]engguna TikTok Shop di Kabupaten Tasikmalaya) - Nabila Lutfiyyah; Herawati Herawati (Universitas Dharmawangsa, 2026)
The rapid advancement of digital technology has significantly transformed consumer behavior, particularly among Generation Z. This study investigates the influence of live shopping features and host interactivity on purchase intention among Generation Z TikTok Shop users in Tasikmalaya Regency. Employing a quantitative approach with descriptive and verificative methods, data were collected from 96 respondents through purposive sampling. Instrument validity and reliability were confirmed (Cronbach's Alpha = 0.876). Classical assumption tests verified normality, absence of multicollinearity, and homoscedasticity. Multiple linear regression analysis revealed that live shopping features (β = 0.683) and host interactivity (β = 0.311) each positively and significantly influence purchase intention, both partially and simultaneously (F = 102.965; sig. = 0.000). The R-Square value of 0.689 indicates both variables explain 68.9% of purchase intention variance. Businesses are advised to consistently optimize live shopping demonstrations and enhance host communication competencies to strengthen consumer engagement and conversion rates.